The Impact of Employer Branding and Career Development on Employee Retention at Al-Ibrah Foundation - Mirza Dwinanda Ilmawan; M. Busyiri Yafi; Rosa Rilantiana; Gatot Kustyadji (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
The purpose of this research is to determine the influence of employer branding and career development on employee retention applied at Al-Ibrah School in Gresik. The sampling was done using the proportionate stratified random sampling method. The sample for this study consisted of 65 respondents who were teachers at Al Ibrah School from kindergarten, elementary school, and junior high school levels. The analysis technique used in this research was multiple linear regression using SPSS software. The analysis results showed that (1) employer branding has a positive effect on employee retention, (2) career development has a positive effect on employee retention, and (3) employer branding and career development have a positive effect on employee retention. This indicates that the employer branding and career development implemented by Al Ibrah School in Gresik are important in retaining teachers who teach at the school.